Pembinaan Guru Madrasah Tsanawiyah Berbasis Budaya Pesantren di Pesantren Nurul Huda Kembang Jeruk dan Pondok Pesantren Al-Jauhariyah Sembung Kecamatan Banyuates Sampang - Shobri, Ach (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2019)
Coaching efforts to improve the quality of Madrasah Tsanawiyah (MTs) based Islamic boarding school teachers are interesting to discuss. As with all educational institutions, it has a distinctive problem style. However, for institutions that are under the auspices of the pesantren the problem is certainly typical of pesantren, as well as the way to solve it. The Chairperson of the Foundation and the ranks of boarding schools together work together to solve the problem-based problem of culture in the pesantren environment, especially the issues related to the development of the teacher's profession. This article, which is the result of a qualitative approach, found an interaction pattern used in teacher training, which is typical of Islamic boarding schools, for example, using routine recitation media once a month, imitation festivals, congregational prayers, silaturrahmi, and others. Whereas in terms of guidance, there are at least four approaches, including; individual, communal, seniority, and utilization of pesantren bureaucracy. From the stakeholder side, Klebun involvement (Village Head), school committees, school principals, and school supervisors provided maximum input oriented to internal and external improvement of institutions, which later had an influence on improving the teaching profession at local educational institutions.